The molecular phylogeny of Chionaster nivalis reveals a novel order of psychrophilic and globally distributed Tremellomycetes (Fungi, Basidiomycota). - Nicholas A T Irwin; Chantelle S Twynstra; Varsha Mathur; Patrick J Keeling (PLoS ONE, 2021)
Snow and ice present challenging substrates for cellular growth, yet microbial snow communities not only exist, but are diverse and ecologically impactful. These communities are dominated by green algae, but additional organisms, such as fungi, are also abundant and may be important for nutrient cycling, syntrophic interactions, and community structure in general. However, little is known about these non-algal community members, including their taxonomic affiliations. An example of this is Chionaster nivalis, a unicellular fungus that is morphologically enigmatic and frequently observed in snow communities globally. Despite being described over one hundred years ago, the phylogeny and higher-level taxonomic classifications of C. nivalis remain unknown. Here, we isolated and sequenced the internal transcribed spacer (ITS) and the D1-D2 region of the large subunit ribosomal RNA gene of C. nivalis, providing a molecular barcode for future studies. Phylogenetic analyses using the ITS and D1-D2 region revealed that C. nivalis is part of a novel lineage in the class Tremellomycetes (Basidiomycota, Agaricomycotina) for which a new order Chionasterales ord. nov. (MB838717) and family Chionasteraceae fam. nov. (MB838718) are proposed. Comparisons between C. nivalis and sequences generated from environmental surveys revealed that the Chionasterales are globally distributed and probably psychrophilic, as they appear to be limited to the high alpine and arctic regions. These results highlight the unexplored diversity that exists within these extreme habitats and emphasize the utility of single-cell approaches in characterizing these complex algal-dominated communities.